Low-temperature fabrication of Bi25FeO40/rGO nanocomposites with efficient photocatalytic performance under visible light irradiation. Issue 17 (6th February 2017) - Wang, Xingfu; Mao, Weiwei; Wang, Qi; Zhu, Yiyi; Min, Yonggang; Zhang, Jian; Yang, Tao; Yang, Jianping; Li, Xing'ao; Huang, Wei
Abstract : Bismuth ferrite/reduced graphene oxide (Bi25 FeO40 /rGO) nanocomposites have been synthesized by a hydrothermal method, followed by a simple room temperature liquid phase process. Abstract : Bismuth ferrite/reduced graphene oxide (Bi25 FeO40 /rGO) nanocomposites have been synthesized by a hydrothermal method, followed by a simple room temperature liquid phase process. Interestingly, X-ray diffraction and scanning electron microscopy analyses indicated that the presence of rGO triggered the transformation of perovskite phase BiFeO3 to sillenite phase Bi25 FeO40 at room temperature, while the spindle-like morphology was maintained. Under visible light irradiation, the obtained Bi25 FeO40 /rGO nanocomposites exhibit high photocatalytic performance for the degradation of methyl orange (MO), suggesting potential applications in photocatalytic and related areas. Furthermore, the function of rGO for the enhancement of photocatalytic activity and the probable mechanism were also discussed on the basis of the results.